2013
DOI: 10.1371/journal.pone.0078694
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Model of Variant Late Infantile Ceroid Lipofuscinosis Recapitulates Behavioral and Pathological Phenotypes of Human Disease

Abstract: Neuronal ceroid lipofuscinoses (NCLs; also known collectively as Batten Disease) are a family of autosomal recessive lysosomal storage disorders. Mutations in as many as 13 genes give rise to ∼10 variants of NCL, all with overlapping clinical symptomatology including visual impairment, motor and cognitive dysfunction, seizures, and premature death. Mutations in CLN6 result in both a variant late infantile onset neuronal ceroid lipofuscinosis (vLINCL) as well as an adult-onset form of the disease called Type A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 90 publications
(172 reference statements)
4
50
0
Order By: Relevance
“…Commonly associated symptoms include cognitive decline, seizures, retinopathy and gait difficulties with patients first reporting to the clinic between two and eight years of age (14)(15)(16). Naturally occurring mouse models for CLN6 and CLN8 diseases have been widely characterized and have been shown to mimic many of the disease phenotypes (17). Like human patients, mutant mice die prematurely and exhibit dysfunctional lysosomal metabolism in multiple tissues and organs (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly associated symptoms include cognitive decline, seizures, retinopathy and gait difficulties with patients first reporting to the clinic between two and eight years of age (14)(15)(16). Naturally occurring mouse models for CLN6 and CLN8 diseases have been widely characterized and have been shown to mimic many of the disease phenotypes (17). Like human patients, mutant mice die prematurely and exhibit dysfunctional lysosomal metabolism in multiple tissues and organs (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Reactive astrocytes have also been described in LINCL and variant late infantile NCL forms (i.e. CLN5 and CLN6), which often precedes neurodegeneration …”
Section: Introductionmentioning
confidence: 99%
“…The selective vulnerability of various populations of neurons is a key feature of many neurodegenerative diseases, including Batten disease ( 27, 28 ). Prior studies have demonstrated that thinning of select anatomical regions and different cortical layers is present in Cln6 nclf mice ( 9, 12, 14, 19 ), however, all of these measurements are based on invasive, histopathological analysis of post-mortem tissues. To identify progressive changes in brain architecture, we examined cohorts of mice longitudinally up to one year of age with T2 weighted magnetic resonance (T2-MRI) and diffusion tensor imaging (DTI).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that by looking at various non-invasive disease markers as a system, rather than individually, we could provide a highly sensitive tool that may be translatable to the clinic. Sample size, endpoints, and rules for stopping data collection were determined based on our previously published studies on this model ( 83 ). No outliers were removed from any data sets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation